2018
DOI: 10.1515/ract-2018-3044
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of naturally occurring radionuclides in soil around a coal-based power plant and their potential radiological risk assessment

Abstract: Coal-fly-ash is one of the major byproducts of coal-based power plant in which naturally occurring radioactive materials (NORMs) are drastically enriched compared to those of feed coals. Thus, improper management of fly-ash may introduce additional radioactivity to the surrounding environment and cause radiological risk. So, in order to study the distribution of radionuclides in soil around a coal-based power plant and to evaluate their radiological risk, soil, coal and fly-ash samples were analyzed by using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 63 publications
(23 citation statements)
references
References 73 publications
3
20
0
Order By: Relevance
“…The risk associated with higher concentrations greater than the permissible limits is grouped into ecological risk and health risk. The HMs in CLS could leach out by the percolating rainwater and carry to natural water and soil sources and even could move great distances in surface water bodies through runoff processes, either suspended on CLS particles or as free ions 6,9 . Besides, HMs are well leached during the weathering and alteration processes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk associated with higher concentrations greater than the permissible limits is grouped into ecological risk and health risk. The HMs in CLS could leach out by the percolating rainwater and carry to natural water and soil sources and even could move great distances in surface water bodies through runoff processes, either suspended on CLS particles or as free ions 6,9 . Besides, HMs are well leached during the weathering and alteration processes.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, due to CLS store in the landfill, potentially hazardous toxic HMs (e.g., As, Cu, Pb, and Zn) in CLS could attribute considerable HM exposure to the environmental compartments, 56 mostly dispersed into the environment causing contamination and deterioration of the quality of soil and water resources. Accordingly, the elevated level of HMs in CLS may lead to modify and enhance the natural background composition of the nearby natural systems and contributing to the surface water, groundwater, and soil, where they can be absorbed, retained, and taken up by vegetables and crops 9 (chronic exposure over a longer time) and consequently accumulated in the bodies of humans, soil, and water organisms, and interact and suffer from HMs poisoning. This eventually results to contaminate and undesired noticeable impact on environmental matrices and adversely affect the animals, humans, vegetables, crop plants (e.g., stunted growth and poor yield), ecosystems, and biodiversity 58 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The textural soil classes for various samples were measured by plotting the outcomes on a triangular diagram devised by Marshal (1947) followed by US Department of Agriculture classification (García‐Gaines and Frankenstein 2015). The pH of the sediment samples was measured using a standard pH meter (model PB‐10; Sartorius) in a mixture of sediment and deionized water in the ratio of 1:2.5 (w/v; Barik et al 2018; Habib et al 2019). The total organic carbon (TOC) content was estimated by the potassium dichromate oxidation method (Schumacher 2002).…”
Section: Methodsmentioning
confidence: 99%
“…Pollutants are released from CTP in different form and stages of the processing system, i.e., before (coal storage, processing), during combustion (flue gas), and after combustion processes and CCRs deposition, transportation, and utilization to the ambient environments as in the form of the gaseous phase, solid, and liquid discharges (Dai et al 2007(Dai et al , 2008(Dai et al , 2012(Dai et al , 2014aDragović et al 2013;Mahur et al 2013;Saikia et al 2014Saikia et al , 2015aSaikia et al , b, 2016Karamanis et al 2009). Some studies working on the NORMs contamination due to the coal-burning appeal for a trivial influence of radioactivity originated from CCRs on the soil environment (e.g., Habib et al 2019b;Papaefthymiou et al 2013;Charro and Pena 2013;Rosner et al 1984), whereas other studies (e.g., Gören et al 2017;Parial et al 2016;Liu et al 2015;Mandal and Sengupta 2006;Ćujić et al 2015Flues et al 2002;Amin et al 2013;Gür and Yaprak 2010;Lu et al 2012aLu et al , b, 2013Dai et al 2007;Bem et al 2002;Papp et al 2002) have demonstrated that a significant augmentation of NORM's content in the soil around CTP, mostly owing to the higher abundance of 238 U and 226 Ra in feed coals and associated CCRs (Table 24.10). However, it is essential to determine the level of NORMs and associated impacts on the ambient environment and on human health around CTPs.…”
Section: Radionuclidesmentioning
confidence: 99%